DINAMIKA PETANI PERKOTAAN - Pepi Rospina Pertiwi (Politeknik Pembangunan Pertanian Bogor, 2020)
The objectives of the study are to describe the level of urban farmer dynamics, thefactors affected the urban farmer dynamics, and the effect of the urban farmer dynamics onfarm enterprise products. The locations of the study are in the area of Jakarta, Depok, andBandung. The results of study indicate that urban farmer has dynamics, shown by urban farmerattitude whereas they have activities which support the dynamics, such as prestative, workhard, autonomous, flexible, and innovative. There are several factors influence the dynamics ofurban farmer, those are farmer’s age, land area, market scope, extention institution, andextention method received by the farmer. Other results are the dynamics effect of urban farmeron farm enterprise product, income and the sustainability of farm enterprises. In conclusion,therefore government attention to urban farmers is needed in order to rise their dynamics. Inaddition, it is also needed to give an opportunity to rise their bargaining position that can pushthem to keep dynamics in doing their job, which subsequently give a positive effect for theirwelfare.